Revisions to the Special Data Dissemination Standard and Establishment of the Special Data Dissemination Standard Plus-Proposed Decisions. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
The purpose of the Special Data Dissemination Standard (SDDS) is to guide member countries in the dissemination of comprehensive, timely, accessible, and reliable economic and financial statistical data in the context of increasing economic and financial integration. The SDDS not only prescribes that subscribers disseminate certain data categories, but also prescribes that subscribers disseminate the relevant metadata to promote public knowledge and understanding of their compilation practices with respect to the required data categories. The purpose of the Special Data Dissemination Standard Plus (SDDS Plus) is to reinforce and supplement the Fund's Data Standards Initiatives and assist Fund members who decide to adhere to the SDDS Plus with regard to the publication of comprehensive, timely, accessible, and reliable economic and financial statistical data in a world of continuing economic and financial integration. The SDDS Plus also requires adherents to disseminate metadata to promote public knowledge and understanding of their compilation practices with respect to the required data categories. The Fund decided that the existing rules governing the SDDS are superseded by the new SDDS legal text. The Fund established the SDDS Plus, which is governed by the rules in the SDDS Plus legal text.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet